Analysis of Factors Influencing The Financial Fraud of Village Funds during The Covid19 Pandemic - Manuhara Putra, Wahyu; Subroto, Bambang; Rahman, Aulia Fuad; Ghofar, Abdul (The International Journal of Accounting and Business Society, 2024)
Purpose—This study aims to examine and analyze the factors that influence financial fraud in the management of village funds during the coronavirus pandemic using the Pentagon fraud theory. Design/methodology/approach—This study examined Village fund financial fraud using the fraud pentagon theory. This research uses quantitative methods. Data was collected through a questionnaire survey and analyzed using the structural equation model in SmartPLS version 2.0. Findings — This study found that financial fraud in village funds was influenced by effective monitoring, the village apparatus's rationality, the village apparatus, and the position of the village apparatus. Practical implications — The central government and village communities must increase monitoring of the use of village funds. Originality/value—This study adds morality as a factor in village fund fraud to the Pentagon fraud theory. Keywords — fraud pentagon; village funds; morality, coronavirus pandemic. Paper type — positive paradigm